S-Scheme CuMn2O4/g-C3N4 heterojunction: fabrication, characterization, and investigation of photodegradation potential of organic pollutants - Masoumeh Yaqoubi; Masoud Salavati-Niasari; Mojgan Ghanbari (Applied Water Science)
Abstract Outstanding photocatalytic performance can be achieved by designing and building heterojunction photocatalysts with a suitable interfacial contact and staggered energy band structure. A simple two-step technique was used to manufacture hybrid inorganic/organic nanocomposites made of copper manganese oxide (CuMn2O4) and g-C3N4. Multiple techniques were employed to characterize the hybridized CuMn2O4/g-C3N4 heterostructure. CuMn2O4/g-C3N4 (0.2:1) efficiently destroyed 91% of erythrosine (10 ppm) below visible lamp in 90 min, being better than the performance of both CuMn2O4 and g-C3N4 and has superior stability. The primary reactive species involved in the photocatalytic breakdown of erythrosine over the nanocomposite were photogenerated superoxide ion radicals. The research results led to the proposal of a photocatalytic mechanism via the nanocomposite for the degradation of erythrosine. Based on the experimental data, a unique S-scheme model was presented to illuminate the charge transport mechanism. This work offers a straightforward method for creating innovative step-scheme photocatalysts for environmental and associated applications. This study revealed that the combination of CuMn2O4 and g-C3N4 as composites shows great potential for efficient photocatalytic dye degradation applications.